MODELAGEM MATEMÁTICA NA EDUCAÇÃO MATEMÁTICA: POSSIBILIDADES PARA O ENSINO E APRENDIZAGEM DA MATEMÁTICA EM SITUAÇÃO DE PRÁTICA PEDAGÓGICA - PONIJALESKI, VANDA VALÉRIA (2023)
This dissertation, titled "Modeling in Mathematics Education: Opportunities for Teaching and Learning Mathematics in Pedagogical Practice Settings," explores aspects of Mathematical Modeling in Mathematics Education, considered as a teaching methodology. It seeks reflections on the guiding question: "What is demonstrated in practices involving modeling in Lower Secondary Education concerning the approaches taken, the mathematical content addressed, and the development of new learning by students?" The objectives are as follows: to identify, after analytical reflections, what is demonstrated in practices involving Mathematical Modeling in Lower Secondary Education and the role of the teacher; to elucidate the approaches related to teaching according to Burak's conception of Mathematical Modeling; to characterize the organization of curricula concerning content in the methodology of Mathematical Modeling as per Burak's conception; and to highlight what emerges concerning students' knowledge construction. To achieve this, a qualitative-interpretative research study was conducted, following the methodologies of Bogdan and Biklen (1994) and Burak (1992; 2004; 2010). The study was implemented at a State School in the municipality of Palmeira, PR, with a 6th-grade class consisting of 30 students, a 7th-grade class with 18 students, and a 9th-grade class with 18 students, where the researching teacher served as the classroom teacher. The findings revealed that Mathematical Modeling, in the adopted approach, plays a significant role in addressing mathematical content and facilitating the development of various forms of learning. It allows students to actively participate in constructing their knowledge, fosters their autonomy in decision-making, and promotes dynamic and enriching classes. Furthermore, it enables the teacher to act as a mediator throughout the process, encouraging continuous reflection on pedagogical practices.